Neuregulin 4 Is a Novel Marker of Beige Adipocyte Precursor Cells in Human Adipose Tissue - Comas, Ferran; Martínez, Cristina; Sabater, Mònica; Ortega, Francisco; Latorre, Jessica; Díaz-Sáez, Francisco; Aragonés, Julian; Camps, Marta; Gumà, Anna; Ricart, Wifredo; Fernández-Real, José Manuel; Moreno-Navarrete, José María (Frontiers in Physiology, 2019)
Background: Nrg4 expression has been linked to brown adipose tissue activity and browning of white adipocytes in mice. Here, we aimed to investigate whether these observations could be translated to humans by investigating NRG4 mRNA and markers of brown/beige adipocytes in human visceral (VAT) and subcutaneous adipose tissue (SAT). We also studied the possible association of NRG4 with insulin action. Methods: SAT and VAT NRG4 and markers of brown/beige (UCP1, UCP3, and TMEM26)-related gene expression were analyzed in two independent cohorts (n = 331 and n = 59). Insulin resistance/sensitivity was measured using HOMAIR and glucose infusion rate during euglycemic hyperinsulinemic clamp. Results: In both cohort 1 and cohort 2, NRG4 and thermogenic/beige-related gene expression were significantly increased in VAT compared to SAT. Adipogenic-related genes followed an opposite pattern. In cohort 1, VAT NRG4 gene expression was positively correlated with BMI and expression of UCP1, UCP3, TMEM26, and negatively with adipogenic (FASN, PPARG, and SLC2A4)- and inflammatory (IL6 and IL8)-related genes. In SAT, NRG4 gene expression was negatively correlated with HOMAIR and positively with UCP1 and TMEM26 gene expression. Multiple linear regression analysis revealed that expression of TMEM26 gene was the best predictor of NRG4 gene expression in both VAT and SAT. Specifically, NRG4 and TMEM26 gene expression was significantly increased in VAT, but not in SAT stromal vascular fraction cells (p < 0.001). In cohort 2, the significant association between NRG4 and TMEM26 gene expression in both VAT and SAT was confirmed, and SAT NRG4 gene expression also was positively correlated with insulin action and the expression of UCP1. Conclusion: Current findings suggest NRG4 gene expression as a novel marker of beige adipocytes in human adipose tissue.